DARI INTERNASIONALISME KE GLOBALISASI: WHAT NEXT? - Indra - Kusumawardhana (Populis : Jurnal Sosial dan Humaniora, 2017)
Since the 1990s, the word "globalization" has become a buzzword to explain how the world is undergoing significant changes. The emergence of new actors in the era of globalization signifies the nature of  Plurality which is now a determination in interaction at the global level. Issues that are now beginning to vary and touch the basic essence to be managed together in the shade of governance between various actors in International System. In fact, before those years, the term internationalism became an important keyword in the contestation and constellation of world politics. Thus, the emergence of the term globalization and internationalism becomes an important marker that there has been a significant shift in world politics. In this context two questions arise; Firstly, the significance lies in the discourse on the concept of internationalism and globalization debating whether these two concepts are an evolution, a transformation, or a continuity? The core argument of this paper propose that the concept of internationalism and globalization is not an evolution, transformation, or continuity, but arises in a different context in world political contestation. Secondly, Therefore the challenges faced in the Era of Globalization are also different, this is because globalization comes from the concept of economy, while internationalism comes from the political concept. What kind of challenges will we face in this Era of Globalization in the future? In order to tackle those two questions; this paper will be divided in two parts. The two discussions made in this paper hopefully can be woven into a sufficient argument to deliver us to a picture of the challenges we will face in the Era of Globalization going forward.